Program Directors' Perceptions of School Counselor Roles. Issue 2 (1st June 2016) - Robertson, Derek L.; Lloyd-Hazlett, Jessica; Zambrano, Elias; McClendon, Levi
Abstract : School counseling program directors hold unique positions as both administrators and school counselors. Research to date has not explored the status of professional school counseling from the perspective of school district level counseling leadership. This phenomenological study reveals insights of eight district level program directors regarding professional challenges and opportunities in school counseling. An overarching theme of moving school counselors from diluted to ideal roles emerged with additional themes of school counselor identity, advocacy, targeted professional development, and synergistic collaboration represented in a working model. Implications for counselor educators, school administrators, school counselors, and school counseling directors are provided.